(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Gastric ulcers conditions can lead to severe complications, including bleeding, perforation, and an increased risk of gastric carcinoma. Natural remedies such as Trianthema portulacastrum may help alleviate these issues by boosting antioxidant defenses and reducing inflammation. In this experiment, thirty Wistar Albino rats were assigned to different groups and observed for 16 days. The study design included several treatment approaches for gastric ulcers. The normal control (Untreated) group was received normal saline for 15 days, while the disease control group also received normal saline for the same period. The Standard Treatment group was received Omeprazole (20 mg/kg) over the 15-day duration. The first test drug group received a daily dose of 250 mg/kg of Trianthema portulacastrum extract for 15 days, while the second Test Group received 500 mg/kg of the extract for the same period. All groups, except the normal control, were administered ethanol (1 mL/200 g, p.o.) on the 16th day. Multiple variables including ulcer index, percentage inhibition of ulceration, antioxidant markers (SOD and CAT), and histopathological analysis of the stomachs of treated rats, were assessed. The methanolic extract of Trianthema portulacastrum (METP) demonstrated potential in treating ulcers. In an ethanol-induced ulcer model, the METP increased SOD and CAT levels, essential antioxidant enzymes that neutralize reactive oxygen species, indicating its capacity to alleviate oxidative stress and inflammation. Notably, the higher METP dose (500 mg/kg) significantly elevated SOD levels, approaching those observed in the normal control group. Both the standard drug Omeprazole and METP markedly reduced ulcer severity, count, and index, while also increasing the percentage of inhibition. The METP exhibited dose-dependent anti-ulcer effects, with the 500 mg/kg dose providing substantial protection against ethanol-induced ulcers. Histopathological studies further supported that Trianthema portulacastrum extracts improve mucosal integrity and reduce lesions. Overall, Trianthema portulacastrum shows promising potential for treating gastric ulcers and enhancing overall health.